I was anastasia ebook A novel. - Lawhon, Ariel (2018)
NEW YORK TIMES BESTSELLER • From the bestselling author of The Frozen River comes a n enthralling feat of historical suspense that unravels the extraordinary twists and turns in Anna Anderson's fifty-year battle to be recognized as Anastasia Romanov. Is she the Russian Grand Duchess or the thief of another woman's legacy? "Tantalizing, surprising, compelling, and utterly fascinating."—Lisa Wingate, New York Times bestselling author of Before We Were Yours Countless others have rendered their verdict. Now it is your turn. Russia, July 17, 1918: Under direct orders from Vladimir Lenin, Bolshevik secret police force Anastasia Romanov, along with the entire imperial family, into a damp basement in Siberia, where they face a merciless firing squad. None survive. At least that is what the executioners have always claimed. Germany, February 17, 1920: A young woman bearing an uncanny resemblance to Anastasia Romanov is pulled shivering and senseless from a canal. Refusing to explain her presence in the freezing water or even acknowledge her rescuers, she is taken to the hospital where an examination reveals that her body is riddled with countless horrific scars. When she finally does speak, this frightened, mysterious young woman claims to be the Russian grand duchess.      As rumors begin to circulate through European society that the youngest Romanov daughter has survived the massacre at Ekaterinburg, old enemies and new threats are awakened. The question of who Anna Anderson is and what actually happened to Anastasia Romanov spans fifty years and touches three continents. This thrilling saga is every bit as moving and momentous as it is harrowing and twisted. Don't miss Ariel Lawhon's new book, The Frozen River!